Role of inducible nitric oxide synthase in the pathogenesis of experimental leptospirosis - Prêtre, Gabriela (2011)
Nitric oxide (NO) produced by inducible nitric oxide synthase (iNOS) is a radical effector molecule of the innate immune system that can directly inhibit pathogen replication. In order to study subsequent iNOS kidney expression in experimental leptospirosis, Golden Syrian hamsters and C3H/HeJ mice were infected intraperitoneally with 107 virulent Leptospira interrogans serovar Copenhageni (LIC). Results showed increased levels of iNOS mRNA and protein in kidneys of infected animals when compared to that in mock-infected animals. To get a deeper insight into the role of iNOS in experimental leptospirosis, both subject species were treated or not treated with 4-aminopyridine (4-AP, 0.3mg/kg), an iNOS inhibitor. Treatment of infected hamsters with 4-AP accelerated the mortality rate to 100% by one day and increased the mortality rate from 20 to 60% in mice at 14 days post-infection. In kidney tissues, 4-AP treatment increased the bacterial burden, as demonstrated through leptospiral DNA quantification by real-time PCR, and aggravated tubulointerstitial nephritis. In addition, iNOS inhibition reduced the specific humoral response against LIC when compared to that in untreated infected animals. According to these results, iNOS expression and the resulting NO have an important role in leptospirosis.